Rethinking homicide : exploring the structure and process underlying deadly situations - Miethe, Terance D. (Cambridge studies in criminology (Cambridge University Press), 2004)
Using multiple data sources and methods, this book involves a micro-historical analysis of the nature of change and stability in homicide situations over time. It focuses on the homicide situation as the unit of analysis, and explores similarities and differences in the context of homicide for different social groups. For example, using Qualitative Comparative Analysis, we investigate whether various social groups (e.g., men vs. women, teenagers vs. adults, strangers vs. intimates, Blacks vs. Whites) kill under qualitatively different circumstances and, if so, what are the characteristics of these unique profiles. The analysis of over 400,000 US homicides is supplemented with qualitative analysis of narrative accounts of homicide events to more fully investigate the structure and process underlying these lethal situations. Our findings of unique and common homicide situations across different time periods and social groups are then discussed in terms of their implications for criminological theory and public policy.